2006
DOI: 10.1007/s00787-006-0531-x
|View full text |Cite
|
Sign up to set email alerts
|

Home treatment for children and adolescents with psychiatric disorders

Abstract: The study examines the effectiveness of home treatment in 70 children and adolescents (aged 6-17 years) with heterogeneous psychiatric disorders. Home treatment was offered to parents/children as an alternative to inpatient treatment (no randomized group assignment). Interventions were carried out by psychiatric nurses (n = 38) and medical students (n = 32) under the supervision of experienced child psychiatrists. Assessment of treatment effects was based on a structured parent interview and parents', children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
1
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 9 publications
3
24
1
11
Order By: Relevance
“…Families that have ongoing contact with the mental health professionals are more likely to recover from the crisis and cope with the situation. Home based treatment programs for children and adolescents with mental disorders appear to be an effective and sustainable strategy for meeting mental health needs in this group [2]. These programs would also be cost effective in countries where the health system is overburdened with infectious diseases and where psychiatric inpatient-care is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Families that have ongoing contact with the mental health professionals are more likely to recover from the crisis and cope with the situation. Home based treatment programs for children and adolescents with mental disorders appear to be an effective and sustainable strategy for meeting mental health needs in this group [2]. These programs would also be cost effective in countries where the health system is overburdened with infectious diseases and where psychiatric inpatient-care is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that a home-based approach has demonstrated reasonable degrees of effectiveness in addressing the following clinical issues: children identified as "seriously emotionally disturbed" or as having a "serious emotional disturbance" (Cherniss and Herzog 1996;Curtis et al 2004;Fuller 2004;Schmidt et al 2006;Sexton and Alexander 2000;Stinchfield 2004;Woodford 1999;Woolston et al 1998;Zarski and Fluharty 1992); children and adolescents exhibiting antisocial behaviors, juvenile delinquents, and those involved with Juvenile Justice Services (Cherniss and Herzog 1996;Curtis et al 2004;Sexton and Alexander 2000;Woodford 1999;Woolston et al 1998;Zarski and Fluharty 1992;Zarski and Zygmond 1989); children with autism (Cottrell 1994); children in need of foster care (Fuller 2004); and families more broadly defined as multiproblem, at-risk, or multi-challenged (Adams and Maynard 2000;Cortes 2004;Johnson et al 2002;Schacht et al1989;Slattery and Knapp 2003;Snyder and McCollum 1999;Zarski and Zygmond 1989). Each of these articles has revealed that families involved in HBFT have experienced greater benefits than those who engaged in traditional, office-based treatment approaches.…”
Section: Indications Specific To Hbftmentioning
confidence: 99%
“…An HBFT approach is often warranted when a family has experienced limited or no change resulting from past treatment efforts employing other treatment modalities (Schmidt et al 2006). Furthermore, HBFT has been indicated when a member has not improved after a series of hospitalizations (Schacht et al 1989;Zarski and Zygmond 1989), his or her condition is directly associated with family interactional patterns, or changes have not resulted in a sustainable resolution of the presenting problems (Fuller 2004).…”
Section: Indications Specific To Hbftmentioning
confidence: 99%
“…Research in child and adolescent psychiatric inpatient therapy programmes is still in its early stages of development and little has been conducted in the field (Schmidt et al 2006). Adapting adult inpatient treatment programmes to suit the specific needs of adolescents is problematic owing to the nature of the environment and the different therapeutic approaches utilised in adult wards (Curran et al 2011).…”
Section: Introductionmentioning
confidence: 99%